Understanding the Operating Mechanisms of Mixed Ionic Electronic Conductors: From Synchrotron-Based 3D Reconstruction to Electrochemical Characterization and Modeling. (2nd June 2015) - Hubert, Maxime; Laurencin, Jérôme; Cloetens, Peter; Couturier, Karine; Lefebvre-Joud, Florence; Bleuet, Pierre; Siebert, Elisabeth
Abstract : A model describing the operation of a Mixed Ionic Electronic conductor (MIEC) has been developed. The main mechanisms and transport phenomena are taken into account. Thanks to a 3D reconstruction obtained by nano-holotomography on a sample prepared with a Plasma Focused Ion Beam (PFIB), the real electrode microstructure has been used into the model. The role of electrode microstructural properties on performances has been estimated through a sensitivity analysis. As the reactive pathways are different in both polarizations, the impact of morphological properties is not the same according to the operating mode. The electrode specific surface area has an effect on the performances and the ratio of the volume fraction to the tortuosity factor of the solid phase has an impact on the electrode response only in cathodic polarization.